Crucial role of subsurface ocean variability in tropical cyclone genesis - Cong Gao; Lei Zhou; I.-I. Lin; Chunzai Wang; Shoude Guan; Fei-Fei Jin; Raghu Murtugudde (Nature Communications)
Abstract The upper ocean provides thermal energy to tropical cyclones. However, the impacts of the subsurface ocean on tropical cyclogenesis have been largely overlooked. Here, we show that the subsurface variabilities associated with the variation in the 26 °C isothermal depth have pronounced impacts on tropical cyclogenesis over global oceans. The sea surface wind stress and its curl before tropical cyclogenesis are large enough to perturb the ocean interior down to more than one hundred meters due to entrainment and upwelling. The 26 °C isothermal depth can fluctuate by tens of meters to significantly modify the upper ocean heat content. Consequently, sea surface temperature anomalies under nascent tropical cyclones are induced, and tropical cyclogenesis is modulated. Our results substantiate an unexpected relation between ocean interior variations and tropical cyclogenesis.